Regulation of FGF2-induced proliferation by inhibitory GPCR in normal pituitary cells - Sosa, Liliana del V.; Picech, Florencia; Perez, Pablo; Gutierrez, Silvina; Leal, Rodrigo Bainy; De Paul, Ana; Torres, Alicia; Petiti, Juan Pablo (Frontiers in Endocrinology, 2023)
Intracellular communication is essential for the maintenance of the anterior pituitary gland plasticity. The aim of this study was to evaluate whether GPCR-Gαi modulates basic fibroblast growth factor (FGF2)-induced proliferative activity in normal pituitary cell populations. Anterior pituitary primary cell cultures from Wistar female rats were treated with FGF2 (10ng/mL) or somatostatin analog (SSTa, 100nM) alone or co-incubated with or without the inhibitors of GPCR-Gαi, pertussis toxin (PTX, 500nM), MEK inhibitor (U0126, 100µM) or PI3K inhibitor (LY 294002, 10 μM). FGF2 increased and SSTa decreased the lactotroph and somatotroph BrdU uptake (p<0.05) whereas the FGF2-induced S-phase entry was prevented by SSTa co-incubation in both cell types, with these effects being reverted by PTX, U0126 or LY294002 pre-incubation. The inhibition of lactotroph and somatotroph mitosis was associated with a downregulation of c-Jun expression, a decrease of phosphorylated (p) ERK and pAKT. Furthermore, SSTa was observed to inhibit the S-phase entry induced by FGF2, resulting in a further increase in the number of cells in the G1 phase and a concomitant reduction in the number of cells in the S phases (p< 0.05), effects related to a decrease of cyclin D1 expression and an increase in the expression of the cell cycle inhibitors p27 and p21. In summary, the GPCR-Gαi activated by SSTa blocked the pro-proliferative effect of FGF2 in normal pituitary cells via a MEK-dependent mechanism, which acts as a mediator of both anti and pro-mitogenic signals, that may regulate the principal effectors of the G1 to S-phase transition.